Assessment of maternal serum β hCG level in pregnancy induced hypertension and normotensive patients and to correlate between the level of β hCG with the severity of pre-eclampsia and eclampsia - Dev, Kapil; Sharma, Anoop; Sood, Rajeev (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Hypertensive disorders during pregnancy are one of the most common medical complication seen during pregnancy, affecting around 5-10% of all pregnancies. Spectrum of this disease ranges from mildly elevated blood pressure with minimal clinical significance to severe hypertension with multi organ dysfunction. Pre-eclampsia complicates about 2-8% of all pregnancies. Pre-eclampsia incidence in India is about 8-10%. Various studies have depicted that, there is a strict relationship between PIH and elevated serum β-hCG level. Methods: This one-year prospective case control study toteled 200 pregnant women attending antenatal care and admitted in eclampsia ward fulfiling the inclusion criteria were studied. Serum βhCG levels were estimated by chemiluminescent microparticle immunoassay. Statistical analysis of data was done by student’s t-test and p-value. Results: The mean β hCG level in PIH patients was found to 36851.59 mIU/ml with standard deviation of 22916.58 while the mean β hCG in normotensive patient was 15433.26 mIU/ml with standard deviation of 6861.56. (p <0.001). The mean β hCG level in gestational hypertensive patients was 25206.19 mIU/ml with a standard deviation of 8696.9. The mean β hCG level in pre-eclamptic patients was 61697.67 mIU/ml with standard deviation of 18498.57. The mean β hCG level were 84106.38 mIU/ml with standard deviation of 11295.05 in the eclamptic patient. The above values were statistically significant (p <0.001). Conclusions: We concluded that there was a striking relation between the PIH including pre-eclampsia and eclampsia with the elevated serum βhCG level. Concluding that early detection of altered serum βhCG shell aid in better management of pre-eclampsia and eclampsia cases which would play a pivotal role in improving the maternal and fetal outcome.